Propriedades físico-químicas de bráquetes e fios ortodônticos utilizados em diferentes tempos de tratamento - Ramos, Aretha Aliny dos Santos (2014)
OBJECTIVE: The focus of this study was to test the hypothesis that treatment time and oral pH had an influence on the physical chemical properties of orthodontic brackets and arch wires. METHODS: 120 metal brackets were evaluated. They were divided into 4 groups (n=30): Group C (Control) and Groups T12, T24 and T36 (brackets recovered after 12, 24, and 36 months of treatment, respectively), rectangular stainless steel arch wires that remained in the oral cavity for 12 to 24 months were also analyzed. Dimensional stability, surface morphology and composition of brackets, resistance to sliding of the bracket/wire set and surface roughness of wires were analyzed by optical microscopy by measurement, scanning electron microscopy and energy dispersive x-ray, universal test machine and atomic force microscopy assays, respectively. Oral pH was evaluated by means of pH indicator strips by the colorimetric method. One-way analysis of variance ANOVA, followed by Tukey multiple comparisons test were used for statistical analysis (p<0.05). RESULTS: There was gradual influence of time from the 12th to 36th month for biofilm and food debris accumulation on bracket surfaces, presence of deformations on winglets and points of corrosion. Occlusal and cervical heights of brackets increased significantly after clinical use for 36 months, compared with new bracket heights (p<0.05). Carbon and Oxygen were shown to be elements that increased expressively and in direct proportion to time, and there was a progressive increase in the coefficient of friction and roughness of wires as a function of time of clinical use after 36 months. Oral pH showed significant difference only between group T36 and its control (p<0.05). CONCLUSIONS: The hypothesis was partially accepted, brackets and orthodontic wires suffered significant physical-chemical changes due to clinical use. However, the treatment time and biofilm and debris accumulation in bracket slots were shown to have more influence on the degradation process and frictional force of these devices than oral pH.